The Etymology Of Medicine And illnesses in Mohet Al Mohet - Habeb , Maher; Hawla, Enas (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
No matter how mature it gets it has to affect and get affected by other languages. leadey to vocabulary exchange from one languages to other The research highlights the new words Arabic and Exotic in Mohet Al Mohet glossary by Al Bostani . The study presents the most important Arabized and Exotic added to Arabic over a period of political instability ,and cultural decline which could be considered the main reason for many new words entry. The study will present the most important words added to Arabic .It will examine those words source and language of origin , and the most important changes that have occurred to those words on the phoneme , morphological , or semantics . the results will demonstrate the most influential languages for Arabic and the reasons behind that The study also will enable identifying the most semantic fields in demand for new vocabulary and highlighting the changes that have occurred to those words .